Combined effects of procurement and collaboration on innovation in public-private-partnerships: a qualitative comparative analysis of 24 infrastructure projects. Issue 6 (3rd June 2022) - Callens, Chesney; Verhoest, Koen; Boon, Jan
ABSTRACT: Different public sector innovation literatures tend to focus on either contractual stimuli or collaborative interactions as sources of innovation. This article argues for a combined approach that integrates these literatures. Using an fsQCA design that exploits rich survey and interview data on 24 PPPs in Belgium and the Netherlands, we confirm the combined effect of contractual stimuli and collaboration. Since PPPs are long-term, contractual collaborations, contractual stimuli and collaborative activities (information sharing, network management) complement and even reinforce each other to create novel ideas. Managers in PPPs that only consider contractual stimuli may therefore fail to innovate.